The Influence of online marketing and Its impact on business in post-covid-19: Sabah tourism industry - Zurina Patrick; Geoffrey Harvey Tanakinjal,; Alesia Sigang Gugkang; Andrew Saw Tek Wei (Universal Publishers, 2024)
Purpose: This research investigates the influence of online marketing and its impact on businesses in the Sabah Tourism Industry post-Covid-19. Design/methodology/approach: The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from 217 industry players who utilize online marketing platforms for business promotion. The data is analyzed to understand cause-and-effect relationships within the proposed model, facilitated by the SmartPLS software. Findings: The research results show that effort expectancy, observability, and social influence do not significantly influence online marketing usage. However, performance expectancy, facilitating conditions, relative advantage, and compatibility significantly influence online marketing usage. Additionally, the adoption of online marketing significantly impacts on business performance. Research limitations/implications: The study focuses on the Sabah Tourism Industry, and the findings may not be generalizable to other regions or industries. Future research could explore a broader geographical scope and include other sectors for a more comprehensive understanding. Practical implications: The existence of online marketing can boost the performance of businesses of all sizes, including small and medium enterprises (SMEs). In the competitive landscape of the tourism industry, where customers demand instant information and personalized experiences, the strategic utilization of online marketing can significantly boost visibility, drive customer acquisition, and foster loyalty. Originality/value: This research highlights the critical factors that influence online marketing usage and its impact on business performance in the Sabah Tourism Industry post-Covid-19, providing valuable insights for industry players to enhance their marketing strategies.